Double Structure Synergy and The Empowering of Poetic Experience in Chairil Anwar’s Poem ‘Senja Di Pelabuhan Kecil’ - Baharuddin Baharuddin (JURNAL ARBITRER, 2023)
The paper studies Chairil Anwar’s poem Senja di Pelabuhan Kecil. It focuses on analyzing the strategies Chairil Anwar applies in manipulating text double structure (the linguistic and literary ones). The data analyzed derives from the poem and in order to illuminate some key terms in the poem, comparison with other poems by the same poet is taken. The analysis of the poem is conducted by elaborating both linguistic and literary approaches. That is conducted by analytically discuss the linguistic devices and their interaction with the structure of literary tropes. It is found that the poet relies much on intensifying the synergy between the two structures. The intensive correlate manifests in the harmonious collaboration between Serial Verb construction and the event seriality; the correlation of morpho-syntactically priming of agent’s role (voice system) and the foregrounding of agent initiation of event (deviation from ordinary use of language). Phonologically considered, the poem shows parallelism between the prosody of line (sound) and the synesthetic (Winter, 2019), the co-perception through vision and hearing sensing. Another essential correlation found constitutes syntactic-phonological pattern which facilitates the representation of encyclopedic experience, which is the rhythm of the speaker’s heartbeat.